Juvenalian Satire In (Selected) Songs Lyric of System of A Downs Band - Muhammad Rifay A. Warouw; Adriansyah Abu Katili; Rusni Podungge (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study examines the use of Juvenalian satire in three songs by System of a Down, namely B.Y.O.B., Chop Suey!, and Toxicity. The research applies Susanna Morton Braund’s theory of Juvenalian satire and Emilio Betti’s hermeneutic approach to uncover the social, political, and moral criticism embedded in the lyrics. Using a qualitative descriptive method, the study analyzes diction, symbolism, irony, sarcasm, and confrontational expressions found in the selected songs. The findings reveal that the songs consistently employ the major characteristics of Juvenalian satire: contemptuous tone, sharp criticism, irony and sarcasm, and provocative confrontation. B.Y.O.B. criticizes war, class inequality, and political hypocrisy; Chop Suey! questions social judgment and moral dogmatism; and Toxicity condemns the destructive effects of modern urban civilization and ideological domination. Through aggressive language and symbolic imagery, System of a Down transforms music into a medium of resistance against injustice and abuse of power. The study concludes that Juvenalian satire remains relevant in contemporary music because it provides a powerful framework for expressing dissent and encouraging critical reflection on social realities.